SURVIVAL ANALYSIS OF PEDIATRIC WILMS TUMOR BASED ON RISK STRATIFICATION - Andy; Sigumonrong, Yacobda Hamonangan (Indonesian Journal of Urology, 2022)
Objective: This study aims to determine prognostic factors of WT patient in Adam Malik Hospital, Medan. Material & Methods: at Adam Malik Hospital, Medan. Univariate and multivariate Cox regression analyses were performed to determine independent prognostic factors for WT. The primary endpoint of this study were patients’ overall survival (OS) obtained by performing Kaplan-Meier analysis on significant variables. Results: From the univariate Cox regression analysis, gender was found to be the sole significant factor (HR = 0.218, p = 0.005) with males have a higher hazard ratio. The multivariate Cox regression analysis yielded age of diagnosis (HR = 13.860, p = 0.014) and incomplete tumor removals (HR = 0.056, p = 0.008). Kaplan-Meier analysis were performed on three significant variables mentioned before. Only gender yielded a significant Mantel-Cox log-rank score (p = 0.002) with male patients were found to have better survivability (which median survival 476 days compared to females’ 11 days). The survival of the boys was 45.45% while all of the girls did not survive until the cut-off. Conclusion: Three prognostic factors, including children’s gender, age of diagnosis, and tumor removal status, were confirmed to be prognostic factors for the overall survival of children with WT. Further studies covering broader demographic areas were suggested to confirm significant results.